A non-invasive method to monitor farmland bird exposure to triazole fungicides. (June 2023) - Fernández-Vizcaíno, Elena; Mougeot, François; Mateo, Rafael; Camarero, Pablo R.; Alcaide, Vicente; Ortiz-Santaliestra, Manuel E.
Abstract: The treatment of seeds with pesticides is an extended practice in current agriculture. There is a high risk of exposure in granivorous birds, such as the red-legged partridge ( Alectoris rufa ), that can consume those seeds remaining on the surface during sowing. Fungicide exposure could in turn affect bird reproductive capacity. To better understand to what extent triazole fungicides are a threat to granivorous birds, we need an easy and reliable method to quantify field exposure. In this study, we tested a novel non-invasive method to detect the presence of triazole fungicide residues in farmland bird faeces. We experimentally exposed captive red-legged partridges to validate the method, and then applied it in a real scenario to assess exposure of wild partridges. We exposed adult partridges to seeds treated with two formulations containing triazole fungicides as active ingredients: Vincit®Minima (flutriafol 2.5%) and Raxil®Plus (prothioconazole 25% and tebuconazole 15%). We collected two types of faeces (caecal and rectal samples) immediately after exposure and 7 days later and quantified the concentrations of the three triazoles and their common metabolite (1, 2, 4-triazole). The three active ingredients and 1, 2, 4-triazole were only detected in faeces collected immediately after exposure. Triazole fungicide detection rates in rectal stool were 28.6%, 73.3% and 80% for flutriafol, prothioconazole and tebuconazole, respectively. In caecal samples, detection rates were 40%, 93.3% and 33.3%, respectively. 1, 2, 4-triazole was detected in 53% of rectal samples. For an applied use of the method in the field, we collected 43 faecal samples from wild red-legged partridges during autumn cereal seed sowing and found detectable levels of tebuconazole in 18.6% of the analysed wild partridges. The results of the experiment were then used to estimate actual exposure levels from this prevalence value found in wild birds. Our study shows that faecal analysis can be a useful tool to assess farmland bird exposure to triazole fungicides, when samples are fresh and the method has been validated for the detection of target molecules. Graphical abstract: Image 1 Highlights: We analysed faeces to detect recent exposure of birds to triazole fungicides. Tebuconazole and prothioconazole have high detection rate in rectal faeces. Flutriafol should be preferentially monitored through the metabolite 1, 2, 4 triazole. Fecal analysis was proven as a valid method to monitor exposure of wild birds.